Learning Outcomes for Students Junior High School: Entrepreneurship-Based Learning Video - Reza Elsinta Utami; Asni Johari; Evita Anggereini (Integrated Science Education Journal, 2023)
Purpose of the study: This study aims to develop entrepreneurship-based learning video media on environmental pollution material and its application in science learning in junior high school. Methodology: This research is classified as research and development using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects used were 24 students and 2 teachers to see responses to entrepreneurship-based learning videos using purposive sampling. Data analysis used descriptive statistics (Category, Min, and Max) and inferential (One paired t-test). Main findings: In this study, the results of validation by material experts and validation by media experts were very feasible. The results of the science teacher's responses and student trials in one-on-one, small, and large group trials were obtained in the very good category. And there are significant differences for students in using Entrepreneurship-based learning videos Novelty/Originality of this study: In the era of the industrial revolution and social revolution, human resources are needed to go through this. Therefore, especially in junior high schools, teachers must carry out innovations, one of which is to innovate in the learning media used, namely using entrepreneurship-based learning videos. Today's students must have an entrepreneurial spirit or attitude to compete in the present.